CMTM6 and CMTM7: New leads for PD‐L1 regulation in breast cancer cells undergoing EMT. Issue 6 (16th May 2022) - Xiao, Malina; Duhem, Caroline; Chammout, Anwar; Berchem, Guy; Janji, Bassam
Abstract: Programmed death‐ligand 1 (PD‐L1) expression has long been used as a biomarker to stratify patients with cancer who will benefit from anti‐PD‐1/PD‐L1 immunotherapy. However, the use of PD‐L1 as a biomarker to guide treatment decisions has recently been called into question due to its dynamic and heterogeneous expression within each tumor and among different tumors as well as during tumor cell plasticity. Therefore, understanding the molecular basis of PD‐L1 expression would enable delineating its value as a reliable biomarker in the clinic. Here, we provide our perspective on the involvement of CMTM6 and CMTM7 as new lead candidates for the regulation of PD‐L1 in breast tumors undergoing an epithelial to mesenchymal transition.